Ответы и объяснения

2013-09-22T16:13:31+00:00
Решение: 
1) cosx=sinx 
tgx=1 
x=π/4+πn 

2) sin2x+2sinx=cosx+1 
2sinx*cosx+2sinx-(cosx+1)=0 
2sinx(cosx+1)-(cosx+1)=0 
(cosx+1)(2sinx-1) 
a) cosx+1=0 
cosx=-1 
x1=π+2πn 
б)2sinx-1=0 
sinx=1/2 
x2=(-1)^nπ/6+πn 

3) sinx+sin3x=0 
2sin2x*cos(-x)=0 
a) sin2x=0 
2x=πn 
x1=πn/2 
б) сosx=0 
x2=π/2+πn 

4) 2sin2x+3cos2x+2sinx=0 
4sinx*cosx+2sinx+3(2cos²x-1)=0 
2sinx(2cosx+1)+3(2cosx+1)(2cosx-1)=0 
(2cosx+1)(2sinx+6cosx-3)=0 
a) 2cosx+1=0 
cosx=-1/2 
x1=±2π/3+2πn 
б) 2sinx+6cosx-3=0 
4sin(x/2)*cos(x/2)+6cos²(x/2)-6sin²(x/2)-3cos²(x/2)-3sin²(x/2)=0 
4sin(x/2)*cos(x/2)+3cos²(x/2)-9sin²(x/2)=0 
9tg²(x/2)-4tg(x/2)-3=0 
пусть tg(x/2)=t 
9t²-4t-3=0 
t1=2+√31 
t2=2-√31 
a) tg(x/2)=2+√31 
x/2=arctg(2+√31)+πn 
x3=2arctg(2+√31)+2πn 
б)tg(x/2)=2-√31 
x/2=arctg(2-√31)+πn 
x4=2arctg(2-√31)+2πn 

5) 2sin2x+cos2x=3sinxcosx 
Решается как предыдущее через тангенс х